2010
DOI: 10.1371/journal.pone.0012399
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Human and Rat Hepatic Lipid Metabolism by the Grapefruit Flavonoid Naringenin: Role of PPARα, PPARγ and LXRα

Abstract: Disruption of lipid and carbohydrate homeostasis is an important factor in the development of prevalent metabolic diseases such as diabetes, obesity, and atherosclerosis. Therefore, small molecules that could reduce insulin dependence and regulate dyslipidemia could have a dramatic effect on public health. The grapefruit flavonoid naringenin has been shown to normalize lipids in diabetes and hypercholesterolemia, as well as inhibit the production of HCV. Here, we demonstrate that naringenin regulates the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
141
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(173 citation statements)
references
References 58 publications
11
141
3
2
Order By: Relevance
“…NRG has been reported to posses several effects on biological system such as antioxidant (Rice-Evans et al, 1996;Cao et al, 1997), anti-inflammatory (Manthey 2000), anticancer (Goldwasser, 2010), antifibrogenic (Lee et al, 2004) and antiatherogenic (Lee et al, 2001). The beneficial effects on human health are mainly due to their antioxidant activity and ability to chelate metals, to scavenge oxygen free-radical, to inhibit enzymes and to prevent oxidation of low-density lipoproteins (LDL) (Madsen et al, 2000;Yu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…NRG has been reported to posses several effects on biological system such as antioxidant (Rice-Evans et al, 1996;Cao et al, 1997), anti-inflammatory (Manthey 2000), anticancer (Goldwasser, 2010), antifibrogenic (Lee et al, 2004) and antiatherogenic (Lee et al, 2001). The beneficial effects on human health are mainly due to their antioxidant activity and ability to chelate metals, to scavenge oxygen free-radical, to inhibit enzymes and to prevent oxidation of low-density lipoproteins (LDL) (Madsen et al, 2000;Yu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the phytoestrogen daidzein protected cortical neurons in an experimental in vitro stroke model; this neuroprotection was due to an increased PPARg activity without direct binding to the receptor (Hurtado et al, 2012). The flavanone naringenin activates both PPARa and PPARg, and induces PPRE-driven gene expression in human hepatocytes (Goldwasser et al, 2010). A recent study reported that naringenin can protect the brain and prevent oxidative stress and NF-kB-mediated inflammation in a rat model of focal ischemic stroke (Raza et al, 2013).…”
mentioning
confidence: 99%
“…Otros estudios realizados con el flavonoide naringina han demostrado que normaliza los lípidos en diabetes e hipercolesterolemia a través de los receptores activados por proliferadores de peroxisoma (PPARs) tales como: PPARα, PPARγ y el receptor hepático X alfa (22) .…”
Section: Discussionunclassified